Biofilm developed on plant substrates enhances growth and survival of post larvae of Macrobrachium rosenbergii - Madathumpady Thomas, Shilta; Lalramchhani, Christina; Lalrinsanga, P. L.; Pillai, Bindu (Fishery Technology, 2020)
A five-week laboratory experiment was conducted to evaluate the efficacy of plant-based substrates for biofilm production and their effect on water quality as well as growth and survival of freshwater prawn Macrobrachium rosenbergii (De Man, 1879) postlarvae. The experiment consisted of three treatments with a control, each with three replicates following a completely randomized design. The substrates evaluated were dried sugarcane bagasse (T1), paddy straw (T2) and Eichhornia (T3). Tanks without substrates acted as control. Seven days after the introduction of substrates at the rate of 300 g /tank, post-larvae were stocked at 40 nos/m2. The mean initial length and weight of the post-larvae was 10.3 mm and 0.008 g, respectively. The post-larvae were fed with commercial pellet feed (30% protein) at 20% of initial biomass. Results revealed significantly higher (p<0.05) levels of total ammonia- nitrogen, nitrite-nitrogen and nitrate-nitrogen in the control tanks (0.07 ±.004 mg L-1; 0.03 ±.01 mg L-1; 1.40 ±.05 mg L-1, respectively) compared to treatment tanks. Addition of natural substrates enhanced survival and growth of post-larvae with highest growth recorded in paddy straw (0.15 ±0.05 g) followed by sugarcane bagasse (0.14±0.04 g) and Eichhornia (0.10±0.01 g) treatment. The enhancement of growth of PL in natural substrate corresponds to the heterotrophic bacteria that are using the substrate, probably as a food resource and as a probiotic. Further, there was no water exchange during the experimental period, which indicated that the presence of a biofilm reduces the necessity of water exchange and saves water during the postlarval rearing of M. rosenbergii at this density.